Structural basis for the inhibition of Plasmodium falciparum glutathione S-transferase by bromosulphophthalein: insights from structure-function studies - Olfsen, Jessica (My University, 2020)
Malaria, caused by the protozoan parasite Plasmodium, is the second most common cause of infectious disease-related death in the world. The species responsible for most of the deaths is Plasmodium falciparum. Presently, there are limitations of current drugs for malaria including inhibitors that are specific for their target. P. falciparum glutathione S-transferase (PfGST) has emerged as a promising therapeutic target as it is one of the several components that are responsible for maintaining the redox balance in the malaria parasite. Therefore, this study aimed to understand the inhibition of PfGST by bromosulphophthalein (BSP), a non-substrate anionic ligand. Recombinant PfGST was over-expressed in Escherichia coli and purified using metal affinity chromatography. The enzyme has been purified and the specific activity was assessed using the glutathione-1-chloro-2,4-dinitrobenzene (GSH-CDNB) conjugation reaction, in the presence and absence of BSP. Once inhibition was evident, an IC50 was performed. Extrinsic fluorescence spectroscopy was then performed in order to determine the binding of BSP to PfGST. The thermodynamics of the PfGST-BSP interaction was then determined, using isothermal titration calorimetry (ITC). Crystal studies, along with molecular modelling was done in order to determine the binding site of BSP. The specific activity of PfGST in the absence and presence of BSP was 0.84 μmol/min/mg and 0.34 μmol/min/mg respectively, at concentration of 537μM, BSP inhibits the PfGST by 50 %. The KM of PfGST was 5.41 mM for GSH. Fluorescence spectroscopy suggests that BSP binds near the H-site of the enzyme, therefore, inhibiting the conjugation of glutathione to CDNB at the G-site. ITC showed that PfGST has two types of co-operative binding sites for BSP which are exergonic. The low affinity site was proposed to be BSP binding to the H-site, which was enthalpically favourable and entropically unfavourable. The high affinity site was proposed to be BSP binding in the L-site, which was which enthalpically unfavourable and entropically favourable. The binding of BSP at the L-site was supported by molecular docking and dynamics studies. The top ranked pose had a negative Glidescore and a Glide emodel score of -9.08 and -122.35 kcal.mol-1 respectively, which suggests tight binding of BSP to the L-site. Both in-silico studies showed that TYR 108 of PfGST was a key residue in π-π interaction with BSP. The interaction of TYR108 and the ligand has been showed in other enzyme studies as a key interaction in the inhibition of the enzyme. Therefore, the detoxification and redox balance activities of PfGST is paramount for the survival of the parasite; hence, BSP could be a valuable inhibitor of this important biological processes within the parasite
A thesis submitted in fulfillment of the requirements for the degree Masters of Science in Molecular and Cell Biology in the Faculty of Science, University of Witwatersrand, 2020